Interactive Sculpting of Digital Faces Using an Anatomical Modeling Paradigm. (12th August 2020) - Gruber, A.; Fratarcangeli, M.; Zoss, G.; Cattaneo, R.; Beeler, T.; Gross, M.; Bradley, D.
Abstract: Digitally sculpting 3D human faces is a very challenging task. It typically requires either 1) highly‐skilled artists using complex software packages for high quality results, or 2) highly‐constrained simple interfaces for consumer‐level avatar creation, such as in game engines. We propose a novel interactive method for the creation of digital faces that is simple and intuitive to use, even for novice users, while consistently producing plausible 3D face geometry, and allowing editing freedom beyond traditional video game avatar creation. At the core of our system lies a specialized anatomical local face model (ALM), which is constructed from a dataset of several hundred 3D face scans. User edits are propagated to constraints for an optimization of our data‐driven ALM model, ensuring the resulting face remains plausible even for simple edits like clicking and dragging surface points. We show how several natural interaction methods can be implemented in our framework, including direct control of the surface, indirect control of semantic features like age, ethnicity, gender, and BMI, as well as indirect control through manipulating the underlying bony structures. The result is a simple new method for creating digital human faces, for artists and novice users alike. Our method is attractive for low‐budget VFX and animation productions, and our anatomical modeling paradigm can complement traditional game engine avatar design packages.